Density structures of the upper mantle in the East African Rift System: implications for the evolution of intracontinental rifting - Tao, Wenfeng; Liang, Qing; Chen, Chao (Frontiers in Earth Science, 2024)
The East African Rift System (EARS) provides an ideal natural laboratory for studying the mechanisms of tectonic plate breakup and continental drift, as well as a unique perspective for exploring the maturation process of continental rifting and its drivers. This study combines high-resolution satellite gravity data and seismic tomography model with an integrated geophysical approach to reveal the density structures in the upper mantle of the EARS. The results show that the northeastern to central Congo and Zimbabwe Craton exhibit significant high-density anomalies extending up to 250 km, which is indicative of a thicker and more intact lithosphere. In contrast, the Uganda, Tanzania, eastern and southern Congo, and Kaapvaal Craton show shallow high-density anomalies underlain by low-density anomalies that are clearly derived from the deeper mantle, indicating a thining of the lithosphere with some degree of possible melting at the base. The various rift segments of the EARS exhibit different rift morphologies. The Main Ethiopian Rift and the Kenya Rift of the Eastern Rift Branch show strong low-density anomalies, indicating intense melting, which is much stronger than that observed in the Western Rift Branch. However, the two rifts may have originated from the same mantle uplift in which the low-density anomalies of the Eastern and Western Rift Branches connected in the deep upper mantle. The lower portion of the Malawi Rift exhibits weaker low-denstiy anomalies, which can be observed to the south of the Malawi Rift, extending further south as a continuation of the EARS. Combining the results of previous kinetics simulations and our density perturbation results, it can be inferred that the Eastern Rift Branch is mainly affected by active rifting, while the Western Rift Branch is affected by both active and passive rifting.